(untitled) (Research, Society and Development, 2022)
Losartan potassium is a drug indicated mostly for the treatment of hypertension. The worrisome factor in relation to the side effects of the administration of this drug in the heart, is due to its chronic or indistinct use. Therefore, to investigate the possible damages resulting from this drug, the aim of this study is to analyze, morphometrically, the thickness of the left ventricular layer of the heart of rats treated with different dosages of Losartana and to investigate its possible harmful effects. For this achievement, samples of adult male Wistar rats already belonging to the histological collection of research of the Department of Anatomy of ICB/Unifal-MG were used. The animals were divided into 5 five groups in which they received the following doses: Control group; G10 - treated with Losartan at a dose of 10 mg/kg/day; G30 - treated with Losartan at a dose of 30 mg/kg/day; G50 - treated with Losartan at a dose of 50 mg/kg/day and G70 - treated with Losartan at a dose of 70mg/kg/day. After 14 days of treatment, the animals were euthanized and their hearts removed and processed following the standardized histological procedure. For morphometric analysis, 9 distinct cuts of the heart were selected. Through specific software, left ventricular thickness was measured in μm2 and statistical analysis was performed by means of variance analysis followed by the Tukey test. Based on the results obtained, it was concluded that the use of Losartan in the doses and treatment conditions of this study did not cause significant changes in the left ventricle of the heart.